1988
DOI: 10.1111/j.1524-4725.1988.tb03363.x
|View full text |Cite
|
Sign up to set email alerts
|

Morpheaform Basal Cell Carcinoma in a Young Black Woman

Abstract: Basal cell carcinomas are uncommon in black patients, and morpheaform basal cell carcinomas are an uncommon histologic subtype. This case report describes the rare occurrence of a morpheaform basal cell carcinoma in a relatively young black patient. This patient underwent Mohs micrographic surgery as the primary therapy for this tumor. Some features of morpheaform basal cell carcinomas are reviewed, and basal cell skin cancer in blacks is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…2,42,60,71 In whites, blacks, and Asians, nodular BCC is the most common histopathologic type of BCC. 41,43,72,78,120 There may be a relatively higher incidence of the adenoid type in blacks and Asians. 121,122 The morpheaform variety of BCC is rare in blacks and appears less frequently than in Caucasians.…”
Section: Bccmentioning
confidence: 95%
See 4 more Smart Citations
“…2,42,60,71 In whites, blacks, and Asians, nodular BCC is the most common histopathologic type of BCC. 41,43,72,78,120 There may be a relatively higher incidence of the adenoid type in blacks and Asians. 121,122 The morpheaform variety of BCC is rare in blacks and appears less frequently than in Caucasians.…”
Section: Bccmentioning
confidence: 95%
“…12 The clinical presentation and histologic features of BCC are similar in blacks, Asians, and Caucasians. 42,43,72,98,99 However, Kidd et al demonstrated immunoperoxidase staining for carcinoembryonic antigen in a higher percentage of BCCs in blacks compared with whites, indicating a greater tendency of differentiation toward follicular, eccrine, or sebaceous structures. 100 Most ethnic patients with BCC are elderly and present with asymptomatic, translucent, solitary nodules with central ulceration (Figs 9 and 10).…”
Section: Bccmentioning
confidence: 96%
See 3 more Smart Citations